2020
DOI: 10.2147/ijn.s231214
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Exosome-Delivered c-Met siRNA Could Reverse Chemoresistance to Cisplatin in Gastric Cancer</p>

Abstract: Background: Drug resistance often occurs in the treatment of gastric cancer, which is the main cause of poor prognosis of chemotherapy. c-Met is overexpressed in a variety of tumors including gastric cancer, often leads to poor prognosis of gastric cancer, therefore regarded as a key target for the treatment of gastric cancer. This study aims to determine whether exosomes with si-c-Met could inhibit the resistance to cisplatin in gastric cancer (GC). Methods: The protein expression levels of c-Met in tumor tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…For instance, breast tumor cells were engineered with tumor suppressor miR-134 and let-7 and the deriving EVs were shown to display potent anti-tumor effects [ 26 , 27 ]. Similarly, 293 T cells were successfully transfected with siRNAs against c-Met, or with the anti-miR214 oligonucleotide to obtain anti-tumor EVs [ 28 , 29 ]. The advantages of this method are the low cost and the highly efficient EV loading.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, breast tumor cells were engineered with tumor suppressor miR-134 and let-7 and the deriving EVs were shown to display potent anti-tumor effects [ 26 , 27 ]. Similarly, 293 T cells were successfully transfected with siRNAs against c-Met, or with the anti-miR214 oligonucleotide to obtain anti-tumor EVs [ 28 , 29 ]. The advantages of this method are the low cost and the highly efficient EV loading.…”
Section: Discussionmentioning
confidence: 99%
“…it was reported that drug sensitivity to cisplatin in patients with refractory Gc could be restored by the mechanism of exosomal-anti-mir-214 delivery to Gc cells (121). Studies have revealed that in SGc7901/ddP cells, c-Met sirna delivered by exosomes reversed the resistance to cisplatin and increased the rate of apoptosis (122). exosomal mir-21 derived from M2 macrophage is also involved in the mechanism of chemotherapy resistance in Gc (123).…”
Section: Exosomal Ncrnas As a Novel Target Of Chemotherapy Drug Treatmentioning
confidence: 99%
“…The exosomes loaded with CRISPR/Cas9 induced apoptosis and cisplatin chemosensitivity in ovarian cancer cells [ 198 ]. An increase in apoptosis and chemosensitivity was observed in cisplatin-resistant human gastric adenocarcinoma cells through treatment with si-c-Met containing exosomes derived from human kidney epithelial cell line [ 199 ]. Normal intestinal FHC cell-derived exosomes transferred miR-128-3p into oxiplatin resistant CRC cells which induced their chemosensitivity and decreased motility [ 200 ].…”
Section: Cancer Management With Exosomesmentioning
confidence: 99%